2004
DOI: 10.1089/088922204773004978
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Epidemic Spread of HIV Type 1 Subtype A1 among Intravenous Drug Users in Latvia and Slower Spread of Subtype B among Other Risk Groups

Abstract: To investigate the rapid HIV epidemic in Latvia, 97 newly detected individuals were sampled in 2000-2001. To establish the molecular epidemiology we sequenced the env V3 and gag p17 regions of the HIV genome and compared them with reference sequences using phylogenetic analyses. As expected, the vast majority (n = 88; 91%) were intravenous drug users (IDUs) from the Riga region. Also, the majority of the investigated individuals (n = 93; 96%) were found to carry a subtype A1 virus that may have entered the Lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
33
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 20 publications
3
33
0
Order By: Relevance
“…2 We have previously molecularly characterized HIV-1 variants from 97 Latvian patients, who were newly diagnosed between 1995 and 2001 and of whom 89 were IDUs. 3 We found that Latvian IDUs were infected with a subtype A1 virus variant that was similar to the A1 variant found in many other parts of the FSU and that was first described from the Ukraine. 4,5 However, little is known about the transmission patterns in the early phase of the Latvian HIV-1 epidemic and in other transmission groups than IDUs.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…2 We have previously molecularly characterized HIV-1 variants from 97 Latvian patients, who were newly diagnosed between 1995 and 2001 and of whom 89 were IDUs. 3 We found that Latvian IDUs were infected with a subtype A1 virus variant that was similar to the A1 variant found in many other parts of the FSU and that was first described from the Ukraine. 4,5 However, little is known about the transmission patterns in the early phase of the Latvian HIV-1 epidemic and in other transmission groups than IDUs.…”
supporting
confidence: 58%
“…From IDUs we included a proportion of all available samples because our earlier study had shown that most IDUs were infected with closely related subtype A1 viruses. 3 The samples had been collected between January 1998 and October 2005. A majority of the samples (n = 218) were newly sequenced, but 97 sequences were from our previous study.…”
mentioning
confidence: 99%
“…1 Molecular epidemiological studies demonstrated that of these two viruses, the IDU-A strains have spread throughout the whole FSU territory and account for around 90% of over a million of HIV-1-infected individuals in the region. 2 These strains are dominating in Azerbaijan, 3 Belarus, 4,5 Georgia, 6 Kazakhstan, 7,8 Latvia, 9,10 Moldova, 11 Russia, 2,12 Tajikistan, 13 Ukraine, 1,14,15 and Uzbekistan 16,17 and are the second (after CRF06_cpx strains) major cause of infections in Estonia. 18,19 In this explosive HIV-1 epidemic in the FSU, Lithuania remains among the least affected countries with 1,900 registered HIV-1 infections (as of January 1, 2012, 0.06% of the population, our own data), with the UNAIDS estimation of the prevalence of HIV-1 in the adult population being 0.1% (all UNAIDS estimations are from www.unaids.org/en/ dataanalysis/tools/aidsinfo/).…”
mentioning
confidence: 99%
“…The first outbreaks of HIV-1 among IDUs in the FSU were reported in 1995 in southern Ukraine (48), followed by rapid spread of the virus in this risk group in the Russian Federation (3,5) and its neighboring countries Belarus and the Republic of Moldova in 1996 (41,50). In 1997, the virus had spread to the Baltic region, inducing a fast-growing epidemic among IDUs in Latvia and later Estonia (2,15,64). Other regions of the FSU also started to experience the rapid growth of IDU HIV-1 infections, such as Kazakhstan, with more than 90% of HIV-1 cases belonging to this risk group (6), and Uzbekistan, with an exponential rise in HIV-1 prevalence among IDUs between 2001 and 2002 (29).…”
mentioning
confidence: 99%